THE ROLE OF PARENTS IN FOSTERING MI STUDENTS’ LEARNING MOTIVATION DURING - Siti Khozanatu Rohmah; Ikhlasul Amal; Yayan Carlian; Anas Salahudin; Titim Fatimah (Al-Mudarris: Journal Of Education, 2022)
Covid 19 cases began to appear in Indonesia in early 2020, the government imposed a Distance Learning (PJJ) policy for elementary to college students during the pandemic. This policy leads to several changes related to the students’ learning methods including its learning motivation. Parents or guardians play an important role in the continuity of learning during a pandemic. This study aims to explore the role of parents in fostering student learning motivation during the covid-19 pandemic. The method used is the Mixed Method with concurrent embedded strategy. The data collection techniques used are questionnaires, observations, interviews, and documents. The data were analyzed using descriptive analysis and by creating thematic codes for the responses of the participants. The result shows that the role of parents in growing motivation to learn at MI is very influential on students' learning motivation because the higher the student's learning motivation, the higher the role of parents in it. The obstacles experienced by parents in motivating students are influenced by the condition of students, the busyness of parents, environmental factors, lack of parental knowledge of the material being taught, and the internet network.